In Vitro and In Vivo investigations on fibronectin coated and hydroxyapatite incorporated scaffolds - Mohamadyar-Toupkanlou, F; Vasheghani-Farahani, E; Bakhshandeh, B; Soleimani, M; Ardeshirylajimi, A (Cellular and Molecular Biology, 2015)
Topological and biochemical aspects of the matrices are essential factors to be extensively studied for more successful tissue engineering. Other characteristics including biodegradability and biocompatibility should be also considered. Nanofibrous structure mimics topography of the natural matrix. Previous in vitro studies reported the favorable effects of nanohydroxyapatite (nHA) and fibronectin (Fn) on biodegradability and biocompatibility of scaffold. Herein, the synergistic outcome of co-application of Fn and nHA incorporation into aligned electrospun polycaprolactone (PCL) seeded by mouse mesenchymal stem cells (MSC) was investigated both in vitro and in vivo. Scanning Electron Microscopy (SEM), contact angle measurement and tensile test were applied for scaffold characterization. In vitro evaluation of the seeded cells was performed by MTT, SEM and cell-cycle analyses. In congruence with in vitro findings, in vivo assessment of four weeks fibronectin coated PCL/ nHA scaffold transplanted mice illustrated the suitable compact surrounding tissue with the most penetrated cells generation. Furthermore, Fn coating resulted in cell infiltration enhancement while nHA addition led to more scaffold biodegradation. In conclusion, fabrication of nanofiberous scaffold with this combination of biochemical composition and surface stimulation caused improved biodegradability and biocompatibility of the scaffold which are desirable in more effective tissue regeneration.